Pengukuran Kesiapan Transformasi Digital Smart City Menggunakan Aplikasi Rapid Miner - Pascalina, Donna; Widhiastono, Raymondhus; Juliane, Christina (Technomedia Journal, 2023)
Digital transformation of organizational change to be more effective and efficient in a city, digital transformation in the city is not yet ready, to determine readiness for change it is necessary to measure readiness in the Smart City Digital Transformation using quantitative data from Human Resources on readiness measurements carried out directly through surveys to all OPD Semarang City. Researchers use Data Mining and Decision Tree C4.5 Algorithm to examine the data, Research uses RapidMiner. The results of this study have an accuracy rate of 82.05% from 36 OPD agencies with 2 rules, namely ready and not ready in the city of Semarang, which are declared not ready with 3 enabler parameters, namely Understanding of Transformation, Cultural Transformation, Competence and Basic Knowledge.